HOX epimutations driven by maternal SMCHD1/LRIF1 haploinsufficiency trigger homeotic transformations in genetically wildtype offspring - Shifeng Xue; Thanh Thao Nguyen Ly; Raunak S. Vijayakar; Jingyi Chen; Joel Ng; Ajay S. Mathuru; Frederique Magdinier; Bruno Reversade (Nature Communications, 2022)
Hox genes are known to control anteroposterior patterning, including the vertebrate spine. Here Xue et al. show that maternal Smchd1 regulates Hox expression in an epigenetic manner, and that wild type offspring from heterozygous mothers show skeletal homeotic transformations as a result of this dysregulation.